2021
DOI: 10.1101/2021.06.18.449071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Requirement for an Otopetrin-Like protein for acid taste in Drosophila

Abstract: Many of the Drosophila receptors required for bitter, sugar and other tastes have been identified. However, the receptor required for the taste of acid has been elusive. In Drosophila, the major families of taste receptors, such as Gustatory Receptors and Ionotropic Receptors are unrelated to taste receptors in mammals. Previous work indicated that members of these major families do not appear to be broadly required acid sensors. Here, to identify the enigmatic acid taste receptor, we interrogated three genes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Recent studies (including this study) have proposed that sour sensation is quite complex in flies compared with sugar or bitter sensation ( Ganguly et al, 2021 ; Mi et al, 2021 ; Rimal et al, 2019 ; Stanley et al, 2021 ). Wild-type females prefer acid-laced food to lay eggs, which is mediated by the expression of IR25a and IR76b in the GRNs of the tarsal segment ( Chen and Amrein, 2017 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Recent studies (including this study) have proposed that sour sensation is quite complex in flies compared with sugar or bitter sensation ( Ganguly et al, 2021 ; Mi et al, 2021 ; Rimal et al, 2019 ; Stanley et al, 2021 ). Wild-type females prefer acid-laced food to lay eggs, which is mediated by the expression of IR25a and IR76b in the GRNs of the tarsal segment ( Chen and Amrein, 2017 ).…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies on IRs and GRs have not been able to conclusively demonstrate their role as molecular sensors for sour taste because none of these studies have demonstrated the direct activation of the IRs by acid. Recently, however, several studies have proposed otopetrin (i.e., a proton-selective channel protein) as a molecular sensor of sour taste in mammals and flies ( Ganguly et al, 2021 ; Mi et al, 2021 ; Tu et al, 2018 ). These studies have demonstrated the direct activation of the otopetrin channel coupled with deficits in acid-mediated behavior, suggesting that this evolutionarily conserved channel protein has a role in proton sensing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that OTOP1 is the sour taste receptor in mice (Zhang et al, 2019) and OtopLA is the sour taste receptor in Drosophila (Ganguly et al, 2021;Mi et al, 2021). The functions of Otopetrins are highly consistent in various species, suggesting that Otopetrin1 may function as the universal sour taste receptor (Frank et al, 2022).…”
Section: Otopetrin Knockout Mutants Do Not Affect Acid Avoidance Beha...mentioning
confidence: 93%
“…Furthermore, Otop1 knockout mice have significantly reduced taste receptor neural responses to both hydrochloric acid and citric acid stimulation (Teng et al, 2019) indicating that OTOP1 is definitely the sour receptor in mice (Zhang et al, 2019). In addition, the Otopetrin-like protein OtopLA is also the sour taste receptor in Drosophila (Ganguly et al, 2021;Mi et al, 2021), suggesting that the Otopetrin1 may function as the universal sour taste receptors across species (Frank et al, 2022). However, it remains unknown whether other Otopetrin channels are required for acid sensation, or they are involved in avoidance behaviors in response to aversive acidic pH.…”
Section: Introductionmentioning
confidence: 99%
“…Most vertebrate genomes encode two related proteins OTOP2 and OTOP3, that also form proton channels (Tu et al 2018) and are expressed in a diverse array of tissues, including in the digestive tract, where mutations in the corresponding genes have been linked to disease (Tu et al 2018;Parikh et al 2019;Qu et al 2019;Yang, Liu, et al 2019). Functional OTOP channels are conserved across species, including in invertebrates where they play roles in acid sensing and biomineralization (Hurle et al 2011;Tu et al 2018;Mi et al 2021;Ganguly et al 2021;Chang et al 2021).…”
Section: Introductionmentioning
confidence: 99%